Actual Problems of Professional Preparation of the Future Officers to the Work in the Extremal Situations - Lisnichenko, Yurii (Pedagogical Discourse, 2017)
The actual questions of training future officers to work in extreme situations have been discussed in the article. The works of scientists regarding the negative impact of extreme situations on the vocational training of future military officers has been discovered. The analysis of the behavior and activities of military officers in extreme situations has been done. Based on the aggregation of factors that negatively affect the training of future officers of the armed forces of Ukraine, their influence on the formation of professional identity has been described. The main characteristics and types of professional competence of a military professional have been identified by the author. The urgency of combat training tasks has been underlined in conclusion, the correctness of the decision-making and using of knowledge and professional skills by future officers during their training, in particular to implement the proactive operational actions in a non-standard extreme situations, despite their negative impact.